Effects of Organizational Justice on Organizational Commitment - Asim Rahman; Naveed Shahzad; Kiran Mustafa; Muhammad Fayaz Khan; Faizan Qurashi (International Journal of Economics and Financial Issues, 2016)
Organizational justice has been considered as an important contributor for commitment of employees towards their organization. Only two dimensions (Distributive and procedural justice) of organizational justice were focused in this study.  This research study is cross sectional in design. For questionnaires distribution a sample size of 500 employees (subjects) were chosen from three higher education institutions of Khyber Pakhtunkhwa, Pakistan.  Data were analyzed by using arithmetic mean, standard deviation, correlation and regression tools and techniques. Results shown that distributive and procedural justice both have noteworthy and positive effects on the dependent variable (organizational commitment) of the employees.